SUSTAINABLE DEVELOPMENT MARKETING AS A TOOL FOR STRATEGIC TRANSFORMATION OF HOSPITALITY INDUSTRY ENTERPRISES - Stebliuk , N. F.; Horozhankina , N. A.; Nebaba , N. O.; Psarov , I. S. (Systems and Technologies, 2026)
The article is devoted to the justification of the transformation of marketing activities of hospitality industry enterprises in the context of implementing a sustainable development model. In the face of modern global challenges, traditional marketing tools require systematic adaptation to the principles of ethical consumption and environmental responsibility. The concept of sustainable marketing is based on a combination of three interrelated components: economic efficiency of business, social responsibility to the community, and environmental safety. The role of these components as key strategic guidelines that allow hospitality businesses to strengthen customer trust and form sustainable competitive advantages through the transmission of shared values with the guest is revealed. The structure of the main stages of a sustainable development marketing strategy adapted to the conditions of the hospitality industry is presented, which allows transforming the business processes of the enterprise into longterm competitive advantages and increasing its investment attractiveness. The main challenges that hinder the effective operation of hospitality establishments are identified: financial, marketing, legal and environmental. A combination of ABC analysis and Pareto charts was used to rank marketing strategies, which allowed for a clear distinction between management measures according to their level of impact on the adaptability of the enterprise. It was found that focusing on group A (digitalization of booking, personalization of service and implementation of energy-efficient solutions) provides the maximum cumulative effect and covers 76 % of the total significance of all identified strategies. Based on the results of the study, practical recommendations were formed to improve the marketing strategy for the sustainable development of the enterprise, structured according to three ESG vectors: environmental, social, and economic